ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUSISI TAHUN 2019 - Temalagi, Selva; Usmany, Alfrin Ernest Marthin; Tuny, Samstein Napoleon (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
The purpose of this study was to determine the comparison of the company's financial performance before and after Mergers and acquisitions. The population of this study is manufacturing companies listed on the BEI in 2018-2020. Financial performance as measured through financial ratios using the variables return on assets, earnings per share, total asset turnover, current ratio, and debt-to-equity ratio. The type of research used is quantitative. The sampling technique used was purposive sampling with 15 companies listed on the BEI. The hypothesis test used is the Wilcoxon signed-rank test. The results of this study indicate that the variable ratios of return on assets, total asset turnover, current ratio, and debt-to-equity ratio do not show significant differences. However, the earnings per share ratio shows that there is a significant difference before and after the Merger and acquisition.